Sleep Now in The Fire: An Analysis of A Song by Rage Against The Machine Using Marxism - Abdul Azis Turhan Kariko (Humaniora, 2011)
Rage against the Machine is known for their politics as well as their music, which the later helped creating an aggressive-heavy rock-rap genre. Article presents a song by Rage against the Machine band related to ideological movement in America, titled Sleep Now in the Fire. This effort brings an understanding ofideology that is embraced by the band. The method is through literature study. Presentation begins with a short biography of the band, theoretical concepts, and analysis of the song as well its music video. It is concluded that the song represents ideological criticism toward capitalism using Marxism. Both of these lyric and music video represents Marxism as it shares the same movement to fight capitalism—which in this case, Rage against the Machine is using their music, lyric, and video to fight the crime against humanity and cultural imperialism.